18F-FDG PET/CT in Intramuscular Mantle Cell Lymphoma With Elongated Lymphomatous Neurovascular Extension. (April 2019) - Hod, Nir; Levin, Daniel; Anconina, Reut; Ezroh Kazap, Dina; Lantsberg, Sophie
Abstract : Abstract: Skeletal muscle involvement by lymphoma is rare, particularly for mantle cell lymphoma. We describe a 65-year-old man who presented with a rapidly growing left thigh mass. FDG PET/CT characterized the mass as malignant. Interestingly, an unusual hypermetabolic elongated tumorous extension was demonstrated arising from the intramuscular mass disseminating alongside the neurovascular bundle of the thigh up to the groin. Histopathology revealed intramuscular mantle cell lymphoma. In this case, we aim to highlight this interesting FDG PET/CT imaging finding, which can serve as a clue allowing one to strongly suggest lymphoma as the leading diagnosis.